2020
DOI: 10.1186/s12875-020-01352-1
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of patient beliefs and expectations regarding the management of low back pain with guideline recommendations – a cross-sectional study in Germany

Abstract: Background Low back pain is a common reason for patients to seek medical care. Physician non-adherence to clinical guidelines has been observed. We investigated the extent to which patient expectations correspond to recommendations of the German national guideline for management of low back pain (G-LBP) and whether patient characteristics, history of LBP and previous treatment experience are associated with expectations. Methods A cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…On the other hand, no participant was completely adherent in the diagnostic phase, treatment phase and in the use of questionnaires. These findings are in concordance with the study of Bahns et al, 20 Kiel et al 19 and Rutten et al 6…”
Section: Institutional Characteristicssupporting
confidence: 93%
See 4 more Smart Citations
“…On the other hand, no participant was completely adherent in the diagnostic phase, treatment phase and in the use of questionnaires. These findings are in concordance with the study of Bahns et al, 20 Kiel et al 19 and Rutten et al 6…”
Section: Institutional Characteristicssupporting
confidence: 93%
“…In these studies, physiotherapy practices reported discrepancies between the current treatment and the recommendations in the guidelines because they received negative responses from the patients, stating that patients were very focused on pain and expected ‘real’ (hands‐on) treatment instead of (hands‐off) exercise therapy and education 24 . ‘Patient views are strongly influenced by previous treatment experiences and education level’ 19 . In addition to these results, Poitras et al reported in a qualitative study that physiotherapists thought that management recommendations could conflict with patient expectations 23…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations